2019
DOI: 10.3389/fimmu.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

The Long Pentraxin PTX3 Is of Major Importance Among Acute Phase Proteins in Chickens

Abstract: The expression level of acute phase proteins (APPs) mirrors the health status of an individual. In human medicine, C-reactive protein (CRP), and other members of the pentraxin family are of significant relevance for assessing disease severity and prognosis. In chickens, however, which represent the most common livestock species around the world, no such marker has yet gained general acceptance. The aim of this study was therefore, to characterize chicken pentraxin 3 (chPTX3) and to evaluate its applicability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Pentraxin 3 (PTX3) in mammals is required for effective host defense against influenza infection (Reading et al, 2008). In chickens PTX3 is as an acute phase marker of bacterial infection that was undetectable in spleen (consistent with our data) but induced rapidly by infection (Burkhardt et al, 2019). PTX3 was highly-expressed in control BMDM and regulated only marginally by LPS.…”
Section: Resultssupporting
confidence: 90%
“…Pentraxin 3 (PTX3) in mammals is required for effective host defense against influenza infection (Reading et al, 2008). In chickens PTX3 is as an acute phase marker of bacterial infection that was undetectable in spleen (consistent with our data) but induced rapidly by infection (Burkhardt et al, 2019). PTX3 was highly-expressed in control BMDM and regulated only marginally by LPS.…”
Section: Resultssupporting
confidence: 90%
“…PTX3 is rapidly produced and released by mononuclear phagocytes and DCs in response to inflammatory signals (35). In chickens, it was shown to be strongly upregulated post-APEC O1:K1:H7 inoculation (36). Recent findings in mammals have shown that pentraxins are involved in complement activation and amplification via communication with complement initiation pattern recognition molecules, but also via recruitment of complement regulators (37).…”
Section: Discussionmentioning
confidence: 99%
“…PTX-3 is a soluble pattern-recognition receptor that plays a critical role in the innate immune response and is an important marker for the permanent inflammatory reaction [24][25][26]. Some studies have suggested that the serum PTX-3 expression level is low in the healthy population but increases significantly in patients with inflammation and infectious disease [27][28][29].…”
Section: Discussionmentioning
confidence: 99%